PSYCHOLOGICAL WELL-BEING OF PARENTS AS AN INDICATOR OF A CHILD’S PERCEPTION OF FAMILY RELATIONSHIP SYSTEMS - Tillashayxova Xosiyat Azamatovna (Frontline Social Sciences and History Journal, 2024)
The article presents the results of an empirical study aimed at examining the relationship between indicators of parents’ psychological well-being and the child’s perceptions of the family relationship system. Empirical evidence shows that the phenomenon of psychological well-being and the indicators of family relationship systems are interconnected. Parents’ experience of psychological well-being or distress is reflected in the child’s perception of the family relationship system.